Strategi Pembelajaran Deep Learning dalam Pembelajaran - Harjun Harjun; Rizal Rizal; Abdullah Igo BD; Friska Natasya (Indo Publishing, 2026)
This study aims to analyze Deep Learning Learning Strategies in Learning. This study uses the Systematic Literature Review (SLR) method with data sources in the form of national and international journals indexed by Google Scholar, SINTA, and GARUDA for the 2020–2025 period. The search was conducted using keywords related to deep learning and resulted in 20 relevant articles selected based on methodological quality and topic relevance. The literature review states that deep learning strategies emphasize in-depth conceptual understanding, active student engagement, and the ability to connect knowledge to real-world contexts. This approach not only develops cognitive aspects but also fosters 21st-century skills such as critical thinking, creativity, collaboration, and problem-solving. Various studies have shown positive impacts in the form of improved learning outcomes, motivation, higher-order thinking skills, long-term memory, and student independence. Implementation is usually carried out through problem-based learning, project-based learning, reflective discussions, and the integration of digital technology. However, the application of deep learning still faces challenges, such as limited teacher readiness, learning time, and technological infrastructure. Therefore, continuous development through teacher training, adequate facilities, and flexible education policies is needed to optimally implement this strategy to improve the quality of education and prepare students to face global challenges.